Pilosella argyrogaliciana, P. argyrolegionensis and P. megargyrocoma (Asteraceae): three new species from the Cantabrian Mountains (N Spain) - del Egido, Fermín; Mateo, Gonzalo (Lazaroa, 2013)
In this paper, we describe three new species of Pilosella (Asteraceae) from the Cantabrian Mountains (N Spain): P. argyrogaliciana Mateo & Egido, P. argyrolegionensis Mateo & Egido and P. megargyrocoma Mateo & Egido. All of them are intermediate species of P. argyrocoma, endemic to the S, C and NW Iberian Peninsula and N Africa. For each species, we provide a detailed description, together with a discussion and a table with the diagnostic morphological characters used to separate these species from their morphologically closest species. We also provide images of type material.